STUDI KOMPARATIF PENERAPAN PRINSIP KEWAJARAN DAN KELAZIMAN USAHA PADA TRANSAKSI AFILIASI JASA MANAJEMEN SEBELUM DAN SESUDAH BERLAKUNYA PMK NOMOR 172 TAHUN 2023 - Tanisha, Gisella; Setiabudi, Andang Wirawan (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2024)
The Indonesian government released the latest regulation regarding the arm's length principle in transactions affected by special relationships, namely Peraturan Menteri Keuangan No. 172 (PMK-172), effective December 29, 2023. As a multinational company with related party transactions, PT XYZ must adjust to PMK-172 for the tax year after its enactment. Therefore, the author conducts a comparative analysis of the application of the arm’s length principle before and after the enactment of PMK-172 to help PT XYZ ensure its tax compliance. This study aims to determine the suitability of arm’s length principle application by PT XYZ for the tax year before the enactment of PMK-172, to compare the application of arm's length principle before and after the enactment of PMK-172, and to identify potential problems after the enactment of PMK-172. The data collection methods used are interviews and documentation, and the data analysis method used is data and method triangulation. The results of the study concluded that the comparison of the application of the arm’s length principle before and after the enactment of PMK-172 show several differences, including the legal basis, the stages of implementing the arm’s length principle, the preliminary stages, and the corresponding adjustment. Furthermore, it is concluded that the problems that are likely to arise after the enactment of PMK-172 are problems in the documentation of the preliminary stage, differences in interpretation of regulations, an increase in tax disputes, and preference for the selection of transfer pricing methods that emphasize the hierarchical method.